Escape from Cuba : Personal Accounts of Those Who Fled Castro's Regime. - Nunez, Eloy; Vendrell, Ernest G. (McFarland & Company, Incorporated Publishers, 2019)
"In 1959, Fidel Castro assumed power in Cuba after overthrowing the government of Fulgencio Batista. In response, thousands of Cubans fled the island, mostly to the United States. This book tells the stories of these Cubans in exile, all of whom overcame great obstacles to escape the brutal Castro regime. Neither a history of Cuba nor of Castro, this book illuminates the underrepresented legacy of the Cuban Exile Community and celebrates their continued thriving in a new country."--